High diversity and rapid changeover of expressed var genes during the acute phase of Plasmodium falciparum infections in human volunteers - Peters, Jennifer (National Academy of Sciences, 2002)
Plasmodium falciparum erythrocyte membrane protein 1 (PfEMP1) proteins expressed on the surface of P. falciparum-infected erythrocytes undergo antigenic variation by switching the gene expressed within a repertoire of approximately 50 var genes per haploid genome. The switching of PfEMP1 plays an important role in the survival and pathogenesis of the parasite. To understand how a parasite switches its var gene expression in human infections, we investigated the composition and change of var gene transcripts during the acute phase of well-defined laboratory-induced P. falciparum infections in naïve human hosts. Multiple var transcripts, with the same dominant transcript, were identified in samples collected after three to four asexual-parasite cycles in two volunteers infected with cloned 3D7 P. falciparum via mosquito bites. A major change in composition and frequency of var gene transcripts was observed between the culture used to infect the mosquitoes and the parasites recovered from the infected volunteers. A further change was seen when infected blood from a mosquito-infected volunteer was either passaged to other volunteers or cultured in vitro. The diversity of var transcripts did not increase with time. The results suggest that the switch of var gene expression is reinitiated after mosquito transmission and that var genes may rapidly switch from the first gene expressed after liver stage, but subsequent switching occurs at a much lower rate.